PERLINDUNGAN HUKUM TERHADAP ANAK KORBAN KEKERASAN SEKSUAL DI MASA PANDEMI COVID-19 (Studi di Dinas Pengendalian Penduduk, Keluarga Berencana dan Perempuan Perlindungan Anak Kabupaten Langkat) - Dr. Redyanto Sidi, SH, MH; Yohny Anwar; Rizky Ayu (Jurnal Ilmiah Advokasi, 2022)
This research is entitled: "Legal Protection of Children Victims of Sexual Violence During the Covid-19 Pandemic Study at the Department of Population Control, Family Planning and Women's Child Protection (PPKB and PPA Office) Langkat Regency". This study aims to obtain empirical evidence regarding legal protection given to vulnerable children as victims of sexual violence in Langkat Regency. In this study using qualitative analysis.Sources of data in the form of secondary and primary and tertiary data. By using a sociological approach, during the Covid-19 pandemic, it has had a tremendous impact, such as increasing risks regarding economic issues, education, aspects of community life in terms of health, politics, violence against children and their families, high stress levels and even cases of violence. so that it has a significant impact on the lives of the children and their families.Its task is to facilitate the protection and needs of women and children. The Office of Population Control, Family Planning and Women's Child Protection (PPKB and PPA Offices) in Langkat Regency will focus more on handling victims of sexual violence against children. The established institution has a role in prevention, service and rehabilitation efforts. The task of prevention in providing protection for children includes socialization, advocacy, counseling and publication activities. The service tasks carried out are health, law, guidance and counseling.Keywords: Keywords: Protection, Sexual Violence, Covid-19